Pharmacological treatment with galectin-1 protects against renal ischaemia-reperfusion injury - Carlos, Carla P. [UNESP]; Silva, Analice A. [UNESP]; Gil, Cristiane D.; Oliani, Sonia M. [UNESP] (My University, 2018)
Galectin-1 protein (GAL-1) has important anti-inflammatory properties, but related pharmacologic approaches to effectively treat or prevent renal ischaemia and reperfusion injury are highly limited. Here, we investigated the effect of GAL-1 in a renal ischaemia-reperfusion injury rat model and an in vitro hypoxia-reoxygenation model with a proximal renal tubular epithelial cell line. In vivo, pretreatment with GAL-1 attenuated the renal parameters changed by ischaemia-reperfusion/hypoxia-reoxygenation, with recovery of renal function, protecting against influx of leukocytes, cell death and oxidative stress. Ischaemia-reperfusion/hypoxia-reoxygenation was also associated with increased renal endogenous expression of GAL-1 and intercellular adhesion molecule 1 (ICAM-1) plus augmented levels of proinflammatory cytokines IL-1β, TNF-α and MCP-1 and decreased anti-inflammatory IL-10 in urine, all of which were abrogated by GAL-1 treatment. In vitro studies demonstrated renal tubular epithelial cells as an important source of GAL-1 during hypoxia-reoxygenation and confirmed the protective effects of exogenous GAL-1 through downregulation of proinflammatory cytokine release by proximal renal tubular epithelial cells. Collectively, our findings confirm the important anti-inflammatory role of GAL-1 in kidney ischaemia and reperfusion injury and indicate its promising use as a therapeutic approach.